Particles in Tojolabal Mayan Discourse - Brody, Jill (Kansas Working Papers in Linguistics, 1987)
Modal clitic in Tojolabal Mayan cliticize to the first element of the clause. Evidentiality particles indicate the speaker's commitment to the truth of the statement, and temporal/aspectual particles indicate expectability, precedence and durativeness. They function not only to place the speaker in relation to the time and truth of what is said, but also aid in discourse cohesion. The reportative particle b'i occurs in foreground clauses in stories.